All‐Carbon‐Electrode‐Based Endurable Flexible Perovskite Solar Cells. (19th January 2018) - Luo, Qiang; Ma, He; Hou, Qinzhi; Li, Yingxiang; Ren, Jing; Dai, Xuezeng; Yao, Zhibo; Zhou, Yu; Xiang, Lichen; Du, Huayun; He, Hongcai; Wang, Ning; et al.
Abstract: Endured, low‐cost, and high‐performance flexible perovskite solar cells (PSCs) featuring lightweight and mechanical flexibility have attracted tremendous attention for portable power source applications. However, flexible PSCs typically use expensive and fragile indium–tin oxide as transparent anode and high‐vacuum processed noble metal as cathode, resulting in dramatic performance degradation after continuous bending or thermal stress. Here, all‐carbon‐electrode‐based flexible PSCs are fabricated employing graphene as transparent anode and carbon nanotubes as cathode. All‐carbon‐electrode‐based flexible devices with and without spiro‐OMeTAD (2, 2′, 7, 7′‐tetrakis‐( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene) hole conductor achieve power conversion efficiencies (PCEs) of 11.9% and 8.4%, respectively. The flexible carbon‐electrode‐based solar cells demonstrate superior robustness against mechanical deformation in comparison with their counterparts fabricated on flexible indium–tin oxide substrates. Moreover, all carbon‐electrode‐based flexible PSCs also show significantly enhanced stability compared to the flexible devices with gold and silver cathodes under continuous light soaking or 60 °C thermal stress in air, retaining over 90% of their original PCEs after 1000 h. The promising durability and stability highlight that flexible PSCs are fully compatible with carbon materials and pave the way toward the realization of rollable and low‐cost flexible perovskite photovoltaic devices. Abstract : An endurable all‐carbon‐electrode‐based flexible perovskite solar cell is developed, employing graphene as front transparent electrode and carbon nanotubes as back electrode. All‐carbon‐electrode‐based flexible perovskite solar cells with and without the spiro‐OMeTAD (2, 2′, 7, 7′‐tetrakis‐( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene) hole transport material show power conversion efficiencies of 11.8% and 8.3%, respectively. Moreover, flexible devices demonstrate outstanding bending durability and thermal stability.